A review of literature on methods for teaching and learning programming in high schools - Salleh F.H.M.; Redzuan N.A.L.M.; Salleh N.S.M. (IGI Global, 2023)
Programming is arguably one of the most important skills for current as well as future generations to learn. The digital jobs market continues to develop at a rapid rate, with each year more skilled coders in demand. Learning coding should start from an early stage. Recently, many schools have started to teach programming to high school students. However, according to the authors' observations, comparatively less attention has been paid to reviewing the methodologies particularly at high school level. In this chapter, the authors carry out an in-depth qualitative study of the most important research works in this context by discussing strengths and limitations of existing approaches. They also study the possibility of the methods to be applied by public schools in Malaysia by considering the factors of language of communication, implementation and execution, digital divide and teaching and learning time. These reviews are useful to educators and any organization that intends to formulate co-curriculum and propose learning techniques. 2023, IGI Global.